Comparative study of serum ferritin and vitamin D in thalassemia patients with healthy controls - Gombar, Shweta; Parihar, Kiran; Choudhary, Mamta (International Journal of Research in Medical Sciences, 2018)
Background: Thalassemia is the most common genetic disorder in humans; they are encountered among all ethnic groups and in almost every country around the world. Mostly occur in the regions surrounding the Mediterranean sea, hence the name. These are a group of hereditary haemolytic disorders characterized by impairment in the synthesis of globin chains of Hb. The present study aimed to find out the serum ferritin and vitamin D level in thalassemic children in the tertiary care hospital in Bikaner, western Rajasthan, India. Methods: In this study 50 (27 male and 23 female) adult skulls were investigated to determine the type of asterion, its distance from important bony landmarks and also the nearby venous sinuses were measured. Results: Level of serum ferritin was significantly high and vitamin D was significantly low (p-value<0.0001 for both) in thalassemic children. Conclusions: In this study the role of serum ferritin and vitamin D has been explored. The extremely high level of ferritin was found due to the regular blood transfusion and consequent iron overload and low vitamin D was found due to impairment in liver functions among thalassemic children.